Aware : the science and practice of presence : the groundbreaking meditation practice - Siegel, Daniel J., 1957- (TarcherPerigee, 2018)
"This groundbreaking new book from New York Times bestselling author Daniel J. Siegel, M.D., introduces readers to his pioneering, science-based meditation practice. Aware provides practical instruction for mastering the Wheel of Awareness, a life-changing tool for cultivating more focus, presence, and peace in one's day-to-day life. An in-depth look at the science that underlies meditation's effectiveness, this book teaches readers how to harness the power of the principle "Where attention goes, neural firing flows, and neural connection grows." Siegel reveals how developing a Wheel of Awareness practice to focus attention, open awareness, and cultivate kind intention can literally help you grow a healthier brain and reduce fear, anxiety, and stress in your life. Whether you have no experience with a reflective practice or are an experienced practitioner, Aware is a hands-on guide that will enable you to become more focused and present, as well as more energized and emotionally resilient in the face of stress and the everyday challenges life throws your way"--